Interpretation of the Source Language Text as a Means of Adjusting Translation to the Target Language Culture on the Example of Selected 18th Century Translations - Agnieszka Kałużna (Ksiegarnia Akademicka Publishing, 2021)
Interpretacja języka źródłowego jako dostosowanie przekładu do wymogów kultury języka docelowego w oparciu o przykłady wybranych osiemnastowiecznych tłumaczeń